Corporate-Level Strategy, Business-Level Strategy, and Firm Performance - Beard, Donald W.; Dess, Gregory G. (Academy of Management Journal, 1981)
Corporate-level strategy and business-level strategy are operationalized in terms of interindustry and intra-industry variation, respectively. Variables representing both levels of strategy are used in a regression model to explain variation in firm profit performance. Both kinds of variable are found to be significant in explaining variation in firm profitability.